Implementasi Pembelajaran Model Student Teams Achievement Division untuk Meningkatkan Hasil Belajar IPA Siswa di SMP Negeri 9 Mataram - Islamiyah, Hj. (Jurnal Paedagogy, 2022)
This study aims to improve students' science learning outcomes through learning the Student Teams Achievement Division model. This study uses a classroom action research method with the research subject being 29 students of class VIII G SMP Negeri 9 Mataram. This research instrument uses observation sheets and tests. The data analysis technique used descriptive qualitative and quantitative analysis. The results showed that the application of the Student Teams Achievement Division model of learning can improve the science learning outcomes of class VIII G students of SMP Negeri 9 Mataram with an average class average of 58.5 or 50% classical completeness to 77 with 55% classical completeness in the cycle. I, increased to an average of 84 with 83% classical completeness in cycle II. Likewise, the value of student activity where the average value before the action was 72 with 20% classical completeness and an increase of 74.46 with 59% classical completeness in the first cycle, and increased in the second cycle with an average the activeness value is 80.8 with the classical achievement of 83%.